Cascading failures in EV charging network - Ma, Sining; Li, Jie (Frontiers in Physics, 2022)
With the rapid increase of Electric vehicle (EV) penetration, EV charging network become an important infrastructure. This paper studies the configuration of EV charging network from a safety perspective. It is found that cascading failures may happen if one charging station is out of work and its load has to be redistributed to its neighboring stations. The cascading failure model borrowed from network science area is used in the study, and the results show the effects of sys-tem parameters on the network robustness. The results indicate that in order to achieve a good performance, it is better to assign extra load based on neighbors’ degree when a node is over-loaded. On the other hand, the extra load redistribution should not consider the distance between the overloaded node and its neighbors.